PENGEMBANGAN MODUL PEMBELAJARAN MATEMATIKA BERBASIS PROJECT BASED LEARNING UNTUK MENINGKATKAN PEMAHAMAN KONSEP ALJABAR PADA SISWA KELAS VII SMP MUHAMMADIYAH CIPANAS - Ranjani, Nuha Fatin; Wicaksono, Dirgantara (SULIWA: Jurnal Multidisiplin Teknik, Sains, Pendidikan dan Teknologi, 2025)
This study aims to develop a mathematics learning module based on Project Based Learning (PjBL) to enhance the conceptual understanding of algebra among Grade VII students at SMP Muhammadiyah Cipanas. The research employed a Research and Development (R&D) method using the ADDIE development model, which includes the stages of analysis, design, development, implementation, and evaluation. The developed module incorporates a simulated buying and selling activity to connect algebraic concepts with real-life contexts. Expert validation and trial results indicated that the module is feasible for use (average validation score > 4.6) and effective in improving students’ conceptual understanding of algebra (N-Gain = 0.72, categorized as high). The module also received very positive responses from students (average questionnaire score = 4.74). The PjBL module has proven to help students link abstract algebra concepts to real-world situations through trading simulations. Therefore, this PjBL-based mathematics learning module is proven to be feasible, practical, and effective in enhancing students’ conceptual understanding of algebra.